The Effect of Human Resource Training and Development on Improving Teacher Performance at Muntok 1 Vocational School - Yuniarti, Dwi; Lingga, Lingga (Efektor, 2019)
Based on observations made by researchers at SMK Negeri 1 Muntok, the problem that arises is the lack of interest of students to follow the learning process because of the way to teach teachers who are still conventional methods so that students' interest decreases to follow the learning process. This study aims to improve teacher performance in order to influence students' interest in participating in the learning process through training and development of students. The method used in this study is descriptive qualitative, this method is used to reveal the implementation of teacher training and development, which is aimed at improving the performance of SMK 1 Muntok. The purpose of this study was to analyze the effect of training and human resource development on the performance of teachers at SMK Negeri 1 Muntok. This study is useful for students who will continue their education to higher education so that the Muntok 1 State Vocational School can produce students who have high-quality grades. Assessing teacher performance in school is not a simple matter. Need good communication within the school itself to make a good standard of assessment.